2021
DOI: 10.3389/fpsyt.2021.636174
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Blood-Brain Barrier Dysfunction Underlie Neuroprogression in Bipolar Disorder

Abstract: Bipolar disorder (BD) often progresses to a more chronic and treatment resistant (neuroprogressive) course. Identifying which patients are at risk could allow for early intervention and prevention. Bipolar disorder is highly comorbid with metabolic disorders including type II diabetes mellitus (T2DM), hypertension, obesity, and dyslipidemia. Our studies have shown that insulin resistance (IR) is present in over 50% of patients with BD and that IR might underlie the progression of BD. While no confirmed predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 125 publications
(188 reference statements)
0
18
0
Order By: Relevance
“…Campbell and Campbell ( 55 ) hypothesize that the KD might help ameliorate symptoms of bipolar illness by shifting the brain's primary fuel source from glucose to ketone bodies, thereby bypassing existing mitochondrial defects and reducing further mitochondrial injury. Calkin et al ( 56 ) have proposed that insulin resistance, via inflammatory damage to endothelial cells, can compromise the integrity of the blood-brain barrier (BBB) in people with bipolar illness. Interestingly, disruption of the tight junctions critical to BBB structure and function has been observed not only in bipolar illness but also in major depression and schizophrenia ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Campbell and Campbell ( 55 ) hypothesize that the KD might help ameliorate symptoms of bipolar illness by shifting the brain's primary fuel source from glucose to ketone bodies, thereby bypassing existing mitochondrial defects and reducing further mitochondrial injury. Calkin et al ( 56 ) have proposed that insulin resistance, via inflammatory damage to endothelial cells, can compromise the integrity of the blood-brain barrier (BBB) in people with bipolar illness. Interestingly, disruption of the tight junctions critical to BBB structure and function has been observed not only in bipolar illness but also in major depression and schizophrenia ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests, for the first time, that BBB leakage is dynamic and likely an underlying mechanism of neuroprogression in BD, mediated by sensitivity to insulin. 5 Importantly, we found that showing our patient his images of extensive BBB leakage allowed him to finally accept that BD is a medical illness involving the brain. Further, it allowed his wife to better understand that his depressive episode was not simply behavior (implying choice), but rather, symptoms of a psychiatric illness.…”
Section: Learning Pointsmentioning
confidence: 74%
“…These findings were consistent with previous longitudinal studies, which suggest that Hs-CRP levels were positively related to future cognitive impairment and decline in elderly individuals with cardiovascular disease [ 48 ] and euthymic patients with bipolar disorder [ 49 ]. These findings might be related to that Hs-CRP is a vital biomarker for systemic inflammation, and elevation of peripheral inflammation may activate the central nervous system, including brain microglia, serotonin transporter expression, oxidative stress, and decreased neuroplasticity, all potentially contributing to structural and functional brain changes, which all with accumulation can cause cognitive performance-related disease [ 50 ]. Besides, evidence also suggests that there might be shared inflammatory pathways concerning insulin resistance and cognitive impairment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%